2016
DOI: 10.1155/2016/8738972
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Potential of Carica papaya and Vernonia amygdalina in Mice Infected with Plasmodium berghei

Abstract: The study determined if administration of Vernonia amygdalina and Carica papaya plants provides synergistic effects in ameliorating plasmodium infection in mice. Thirty mice (17.88–25.3 g) were divided into 6 groups of 5 mice each. Group 1 was normal control, while groups 2–6 were intraperitoneally inoculated 2.5 × 107 Plasmodium berghei parasitized red blood cell, followed by daily administration of 350 mg/kg aqueous leaf extracts after establishment of infection. Group 2 was disease control, while group 6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
(20 reference statements)
1
21
1
Order By: Relevance
“…12 C. papaya leaf extract showed good in vivo and in vitro antimalarial activities. 13,14 Ocimum sp., P. niruri, Aegle marmelos and M. charantia were also used in India as antimalarials; and showed good recipes for remedy could be a single or a combination of various species of plants or plant parts. To prepare a plant material into medicine, it was processed simply, for example crushing and mixing with a little amount of water or oil for massage; soaking the whole or ground for a mixture of bath water; or boiling with water for a drink.…”
Section: Discussionmentioning
confidence: 99%
“…12 C. papaya leaf extract showed good in vivo and in vitro antimalarial activities. 13,14 Ocimum sp., P. niruri, Aegle marmelos and M. charantia were also used in India as antimalarials; and showed good recipes for remedy could be a single or a combination of various species of plants or plant parts. To prepare a plant material into medicine, it was processed simply, for example crushing and mixing with a little amount of water or oil for massage; soaking the whole or ground for a mixture of bath water; or boiling with water for a drink.…”
Section: Discussionmentioning
confidence: 99%
“…Fatmawaty et al (2017) further buttressed the antiplasmodial activity of C. papaya in P. berghei infected mice and histological examination of liver tissues of treated and untreated mice; which further supports the potential antimalaria of this plant, hence validating its traditional use in the treatment of malaria. Thomas et al (2004), Fatmawaty (2013) and Okpe et al (2016) also reported the antilarvicidal and antimalarial potential of fruit and leaf extract of C. papaya, both in vitro and in vivo. Liver sections of the group treated with C. limon showed reduced inflammatory cellular infiltrates, and the sinusoids were mildly packed with Kupffer cells and haemozoin pigment was seen in various regions.…”
Section: Discussionmentioning
confidence: 98%
“…& Perr., and Cassia sieberiana DC. Chemical extracts from these species have already been shown to inhibit the Plasmodium in experimental models of the blood stage ( Ancolio et al, 2002 ; Sanon et al, 2003 ; Koudouvo et al, 2011 ; Ouattara et al, 2014 ; Abdulrazak et al, 2015 ; Lamien-Meda et al, 2015 ; Okpe et al, 2016 ). It may be the case that these plant species have a general mechanism of action on the liver as antiproliferative, antioxidative, or anti-inflammatory agents with a potent activity against Plasmodium at its hepatic stage ( Mazier et al, 1985 ; Carraz et al, 2006 ); but none of these species had been tested on malaria as yet.…”
Section: Discussionmentioning
confidence: 99%